Consequences of chemical residue formation during potentiation of final irrigation - Mirela Cesar Barros; Jessica de Almeida Coelho; Lidiane de Castro Pinto; Marco Antônio Húngaro Duarte; Flaviana Bombarda de Andrade (Universidade Estadual de Campinas, 2020)
Seeking to increase the efficiency of endodontic irrigation, the association of different solutions as final irrigant has been investigated, such as sodium hypochlorite with chlorhexidine. The literature shows that the combination of these substances leads to the formation of a brownish precipitate, but does not reveal measurements of the intensity of this precipitate and its consequences. Aim: The present study aimed to evaluate the change in dentin color and the obliteration of the dentinal tubules after the association of sodium hypochlorite (NaOCl) with chlorhexidine (CHX) in the final irrigation. Methods: Fifty sterile human lower premolars were prepared with a ProDesign R 35.05 files and divided into 6 groups. Four different NaOCl concentrations (0.5%; 1%, 2.5% and 5.25%) associated with 2% CHX were tested, in addition to 2 control groups, using only 2.5% NaOCl and 2% CHX, respectively. After the final irrigation protocol, the dentin color change was evaluated by spectrophotometry immediately and after 24 hours, and the dentinal tubule obliteration was assessed by scanning electron microscopy. Results: It was possible to verify that regardless the NaOCl concentration used when associated with CHX, a chemical residue was formed, with consequent dentin pigmentation and tubular obstruction. There was a trend towards increased dentin pigmentation and tubular obstruction due to the deposition of the chemical residue formed by this association. Conclusion: It can be concluded that all concentrations of NaOCl associated with CHX caused color changes and tubular obstruction, being proportional to the concentration of NaOCl used.